Vitamin D and Lipid Profiles in Postmenopausal Women: A Meta-Analysis and Systematic Review of Randomized Controlled Trials - Liu, Weiting; Wu, Zezhen; Zhu, Dan; Chen, Genben; Yan, Guiming; Zhang, Shuo; Chen, Fengwu; Khan, Barkat Ali; Hou, Kaijian (Frontiers in Molecular Biosciences, 2021)
Background and Aim: It is known that hyperlipidemia and low vitamin D level are risk factors associated with cardiovascular disease (CVD). However, the effect of vitamin D administration on lipid profiles in postmenopausal women remains unclear. This study aims to evaluate the effect of vitamin D on lipid profiles in postmenopausal women based on meta-analysis and systemic review. Methods: The literature search was performed in multiple databases (Scopus, PubMed/Medline, Web of Science, and Embase) from 1997 to 2021. The statistical analysis was performed using the Stata software version 14 (Stata Corp. College Station, Texas, United States). The effects of vitamin D administration of the lipid profiles, including Triacylglycerol (TG), LDL-Cholesterol (LDL-C), HDL-Cholesterol (HDL-C), and Total Cholesterol (TC) were evaluated by the Der Simonian and Laird random effects model. The weighted mean difference (WMD) and 95% confidence intervals (CI) were calculated. Results: The level of TG changed significantly by −3.76 mg/dl (CI: −6.12 to −1.39, p = 0.004) and HDL-C by 0.48 mg/dl (CI: −0.80 to −0.15, p = 0.004) in vitamin D administration group [11 eligible trials (placebo = 505 participants, vitamin D intervention = 604 participants)] compared to the control group in the postmenopausal women. Taking into account this comparison between groups, in contrast, the level of LDL-Cholesterol (LDL-C) (WMD: 0.73 mg/dl, 95% CI: −1.88, 3.36, p = 0.583) and TC (WMD: 0.689 mg/dl, CI: −3.059 to 4.438, p = 0.719) did not change significantly. Conclusion: In conclusion, the vitamin D administration in postmenopausal women, decreased the concentrations of TG, and HDL-C, but have no effects on LDL-C and TC.